The Power of Story: The Effect of Linguistic Narration in Tourism Promotion on Intention to Visit Bali’s Temples - Denok Lestari; Yang En Siem Evelyn (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
Balinese Hindu pilgrimage sites are well known for their historical and cultural richness that attract visitors all year around. This study investigated the effectiveness of promotional efforts and how the strength of narrative stories could impact on a visitor's intention to revisit Balinese Temples. It focused on Promotion as the Independent Variable (X), Intention to Revisit as the Dependent Variable (Y), and Narration as the Moderating Variable (Z). A quantitative research method using direct observation and in-depth interviews with the temple’s caretakers, the Cultural Board Officer, and the local tour guides were conducted to discover the temples’ history and current condition. An online survey was distributed to 250 respondents and the results were tabulated using the Smart PLS application to analyse the effects of promotion and narration to the intention to revisit. The results of this study showed that the promotion significantly influenced the intention to revisit with P-Value = 0.007, while showing an original sample value of 0.067 and a t-statistic of 0.126, the narration of the temples did not give substantial moderation. However, it is essential to integrate linguistic narration into promotion to boost the improvement of Bali’s pilgrimage sites.